"Delayed start" gonadotropin-releasing hormone antagonist protocol in Bologna poor-responders: A systematic review and meta-analysis of randomized controlled trials. (January 2020) - Cozzolino, Mauro; Franasiak, Jason; Andrisani, Alessandra; Ambrosini, Guido; Vitagliano, Amerigo
Abstract: To evaluate the effectiveness of delay start protocol in improving the success of in vitro fertilization (IVF) in poor responders according to Bologna's criteria. Only randomized controlled trial (RCT) of infertile women undergoing a single IVF/ICSI cycle with ovarian stimulation protocol based on daily injections with delay start protocol or a conventional antagonist protocol were included in this systematic review and meta-analysis. The review protocol was registered in PROSPERO before starting the data extraction (CRD42019128284). Primary outcome was clinical pregnancy rate. Ongoing pregnancy rate, miscarriage rate, number of oocytes, number of MII oocytes, stimulation length, gonadotropin amount and cancellation rate were considered as secondary outcomes. Four randomized controlled trials were included with a total number of 380 participants. 189 patients were included in the delayed start protocol and 191 were allocated to the comparison group. The results showed a significant higher clinical pregnancy rate (CPR) in patients allocated to the intervention. Data from all studies failed to detect a statistical difference between groups in terms of ongoing pregnancy rate (OPR), miscarriage rate (MR), Total-Oocyte, MII-Oocyte and Total-Embryos. Gonadotropin amount (GA) was significantly lower in the intervention group in comparison to controls, with no difference in stimulation length (SL) and cancelled cycle (CC). Delayed start GnRH-antagonist protocol may reduce GA and improve CPR in poor ovarian responder according to Bologna criteria.